2018
DOI: 10.1002/adfm.201705938
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Subphthalocyanine Dyes for Optical Imaging and Therapy of Cancer

Abstract: The family of subphthalocyanine (SubPc) macrocycles represents an interesting class of nonplanar aromatic dyes with promising features for energy conversion and optoelectronics. The use of SubPcs in biomedical research is, on the contrary, clearly underexplored, despite their documented high fluorescence and singlet oxygen quantum yields. Herein, for the first time it is shown that the interaction of these chromophores with light can also be useful for theranostic applications, which in the case of SubPcs comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Over the past 6–8 years, “smart” compounds that possess dual fluorescence sensing and singlet oxygen sensitizing properties have become a hot topic , with success reported in dual function image‐guided and photodynamic therapy applications (PDT) . Indeed, our previous O ‐ and N ‐decyl‐pterins possessed good singlet oxygen quantum yields (Φ ∆ ), but had poor fluorescence quantum yields (Φ F ) some 4–30 fold less compared to native pterin, thereby fulfilling only two of three facets, even though a minor fluorescence increase was observed when intercalated in the membrane .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 6–8 years, “smart” compounds that possess dual fluorescence sensing and singlet oxygen sensitizing properties have become a hot topic , with success reported in dual function image‐guided and photodynamic therapy applications (PDT) . Indeed, our previous O ‐ and N ‐decyl‐pterins possessed good singlet oxygen quantum yields (Φ ∆ ), but had poor fluorescence quantum yields (Φ F ) some 4–30 fold less compared to native pterin, thereby fulfilling only two of three facets, even though a minor fluorescence increase was observed when intercalated in the membrane .…”
Section: Introductionmentioning
confidence: 99%
“…[48,49] In addition, it's intense absorption (550-600 nm) and emission in the visible region owing to its 14-π electron configuration system have attracted widespread attention in the light-harvesting field. [50][51][52][53][54] Numerous studies have demonstrated the potential of SubPcs as functional materials in a variety of applications such as photodynamic therapy (PDT), [55,56] organic field-effect transistors (OFETs), [57] organic light-emitting diodes (OLEDs), [58] and organic photovoltaic cells (OPVs) [59] in the last years. However, the fabrication of SubPcs sensitized semiconductor materials and their properties under visible-light irradiation have rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…They are conic-shaped macrocycles, with a 14-π electron aromatic core. This scaffold is used in many fields, such as organic material [7], photodynamic therapy [8] or optoelectronic [9,10]. Most functionalizations of the SubPc moieties are done by substitution of the axial halogen.…”
Section: Introductionmentioning
confidence: 99%